МЕКТЕП ОҚЫЎШЫЛАРЫНДА ТАРИЙХЫЙ БИЛИМЛЕРДИ ҚӘЛИПЛЕСТИРИЎ УСЫЛЛАРЫ - Ганиев, Т.С. (FAN va JAMIYAT, 2020)
The article deals with the advantages of using pedagogical technologies and interactive methods at the lessons in History.